Eating styles profiles in Chilean women: A latent Profile analysis. (1st August 2021) - Schnettler, Berta; Robinovich, Jossiana; Orellana, Ligia; Miranda-Zapata, Edgardo; Oda-Montecinos, Camila; Hueche, Clementina; Lobos, Germán; Adasme-Berríos, Cristian; Lapo, María; Silva, Jaime; Ossa, Ximena; Muñoz, Sergio
Abstract: The aims of this study were to identify profiles of women based on their levels of emotional, external and restraint eating, and to determine differences in these eating styles profiles based on nutritional status, sociodemographic characteristics, stress, social support, and satisfaction with the body image. Questionnaires were administered to 884 women aged 20 to 60 living in two Chilean cities. Questionnaires included the Dutch Eating Behavior Questionnaire (DEBQ), the Medical Outcomes Study-Social Support Survey, and the Perceived Stress Scale (PSS). Satisfaction with body image was assessed using a body-image-related single question. Nutritional status and sociodemographic characteristics were also assessed. Latent Profile Analysis (LPA) was used to identify profiles based on the three eating styles measured by the DEBQ. LPA allowed to distinguish four eating styles profiles: "women with medium emotional and external eating, high dietary restraint" (Profile 1, 36.64%); "women with low emotional, external and restraint eating" (Profile 2, 25.25%), "women with high emotional, external and restraint eating" (Profile 3, 21.85%); and "women with very low emotional and external eating, low dietary restraint" (Profile 4, 16.26%). Profile 1 had a greater proportion of women moderately satisfied with their body image. Profiles 2 and 4 scored higher in perceived social support and had greater proportions of women satisfied with their body image. Profile 4 had a higher proportion of married or cohabiting women. Profile 3 scored higher in the PSS and had higher proportion of obese and unsatisfied with their body image women. These results suggest that interventions to reduce emotional, external and restraint eating should not only involve the women, but also their family members.